The Influence of Motivation and Work Facilities on Organizational Commitment and its Impact on the Employee Performance at Dinas Perindustrian dan Perdagangan Provinsi Jambi - Zahari, M.; Ali Akbar; Syaifullah Syaifullah (Dinasti Publisher, 2023)
The purpose of this research is to describe the motivation, work facilities, organizational commitment and performance of employee at Dinas Peindustrian dan Perdagangan Provinsi Jambi. Then for analyze the influence of motivation and work facilities on organizational commitment, analyze the influence of organizational culture and style leadership of motivation and work facilities on employee performance , then analyze effect of organizational commitment on the performance of employees, then analyze the influence of motivation and work facilities through organizational commitment to employee performance. This research is a research using descriptive and verification research methods, namely a a method in examining a group of people, an object, situation and condition of a system of thought with the aim of making a description, a systematic picture according to the facts being investigated. The verification research aims to test hypothesis about the influence of the variables of this study. The analytical tools used in this study were track analysis and samples used by census method involving 96 employees. Data were analyzed using SPSS.22. The results of the research show that motivation in high conditions, work facilities in good condition, organizational commitment and employee performance also high , that motivation and , work facilities simulataneously or partial positive and significant effect on Organizational commitment, motivation and work facilities simultaneously and partially have a positive and significant effect on performance employee, and organizational commitment has a positive and significant effect on performance employee at Dinas Peirindustrian dan Perdagangan Provinsi Jambi.